DISKURSUS SUNNAH SEBAGAI SUMBER HUKUM ISLAM: Perspektif Ushuliyyin dan Muhadditsin - Umma Farida (Program Studi Hukum Keluarga Islam, 2015)
Sunnah is the second sources of law after the Qur’an. The understanding of Sunnah according to muhadditsin has wider scope than that of ushuliyyin. This is understandable due the concern of ushuliyyin is sunnah in its role as a source of Islamic law, while muhadditsin classifies everything that comes from the Prophet PBUH as sunnah, whether or not they have legal consequences. This paper captures the discourse on Sunnah according to ushuliyyin and muhadditsin perspective; starting from the definition of Sunnah, its function and classification, including the dichotomy of tasyri’iyyah and ghayr tasyri’iyyah, as well as the meaning and patterns of interaction with the Sunnah in order to obtain a proper understanding of the Sunnah and draw a law from it.